Molecular and Epidemiological Study of Cryptosporidium spp. in Mid-Euphrates Area - Karar M. Abdul-Sada (Kufa Journal for Nursing Sciences)
Objectives: the aim of present study was to search for Cryptosporidium spp. in our children and tracking different epidemiological effects.